O poder de direção do empregador e o descumprimento de normas de interesse público: exigência de vacinação do empregado contra Covid-19 - Mattosinho, Cassiano Baptista (2022)
This dissertation has the general objective of analyzing, in the light of a counterpoint between rules of public interest and the directive power of the employer, the possibility of termination of the employment contract for just cause of an employee who unjustifiably refuses to be vaccinated in times of a pandemic. The problem highlighted in this study can be reduced to the following question: to what extent, analyzing the necessary observance of public interest norms and the directive power of the employer within the organization, is there a possibility of termination of the employment contract for just cause of an employee who unjustifiably denying vaccination in times of a pandemic? To answer it, a bibliographic and jurisprudential survey was carried out to collect the elements, being, therefore, an exploratory research, with a qualitative approach to the problem. Data analysis is content critical. The development chapters were built with a view to responding to the specific objectives of the research, so that, initially, we sought to conceptually approach the directive power. In to this, it was about employment relationship. Having done that, we sought to list the legal hypotheses for terminating the employment contract with just cause. Subsequently, attention was focused on the analysis of the Direct Action of Unconstitutionality 6.586, Ordinance 620 of the Ministry of Labor, and Action for Noncompliance with Fundamental Precept n.0 898, highlighting the need or not for vaccination of all those who are part of a group of workers in the same work environment. The results obtained showed that, although the issue has not been definitively addressed by the Federal Supreme Court, since the Action for Noncompliance with Fundamental Precept 898 is pending judgment, the tendency is for the interests of the collectivity to prevail over those of the individual. Thus, the employer can be recognized the right to use its directive power to apply just cause to employees who, unjustifiably, refuse to be vaccinated in times of pandemic, thus ensuring the right to health of other employees. of the company, fulfilling its constitutional mission of ensuring a safe, healthy and healthy work environment for all